J.K.ROWLING VA C.S.LEWISNING ASARLARINI QIYOSLAB, HARAKTER HAMDA MUNOSABATNI OCHIB BERISHDA DIALOGLARDAN FOYDALANISH - Kurbanova Sayyora Komiljanovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the significance of dialogue in the literary works of J.K. Rowling and C.S. Lewis, focusing on its role in character development and relationship dynamics. From Rowling's Harry Potter series and Lewis's The Chronicles of Narnia, the study identifies their distinct dialogue styles-Rowling's casual and relatable tone versus Lewis's formal and philosophical approach. Through qualitative analysis of dialogue excerpts, the study categorizes linguistic characteristics, emotional resonance, and thematic implications. Results indicate that Rowling's dialogue fosters relatability and humor, enhancing emotional connections with characters, while Lewis's dialogue emphasizes moral insights, contributing to thematic depth. Ultimately, the analysis underscores the power of dialogue as a literary device and recommends further exploration of its impact on character evolution in literature.